Tuning and Effectiveness in Heritage Models - Jenny Richards; Peter Brimblecombe (Heritage, 2023)
Modelling can explore heritage responses to environmental pressures over wide spatial and temporal scales, testing both theory and process. However, compared to other fields, modelling approaches are not yet as common in heritage management. Some heritage models have become well known, though they struggle to have an impact beyond academia, with limited practical applications. Successful models appear to be adaptable to multiple sites or objects, intuitive to use, run using widely available software and produce output translatable into practical actions. Model tuning is also vital for the model to be effective. A specific purpose should be determined from the outset to enable tuning in the earliest design stages. Heritage models can be developed to explore theories or processes that affect or interact with heritage. Input should also be tuned to relevant temporal and spatial scales and consider duration and location. Additionally, it is important to account for materials and elements specific to heritage. Models need to be useful and usable if they are to be effective. User-friendly programs and interfaces help practical use. However, success can create problems, as input and output could become socially or commercially sensitive. The wider use of models may require broader discussion among heritage professionals and the provision of training.